FAKTORFAKTOR RISIKO STROKE PADA PENYAKIT GINJAL KRONIK STADIUM V YANG MENJALANI HEMODIALISIS (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION CHRONIC KIDNEY DISEASE CKD AND ENDSTAGE RENAL DISEASE ARE ASSOCIATED WITH A SIGNIFICANTLY IN CREASED RISK OF STROKE INCIDENCE AND MORTALITY OF STROKE IN CKD PATIENTS IS HIGHER RATHER THAN AMONG THE GENERAL POPULA TION STROKE IN HEMODIALYSIS PATIENTS IS ALSO ASSOCIATED WITH HIGH MORTALITY